Perancangan Sistem Informasi Arsip Data dengan Metode Incremental Model pada Kantor Abie Property - Bagus Putra Pratama Effendi; Mitha Caroline S.; Rama Wiranata Kusumah (CV. Multi Kreasi Media, 2026)
This study aims to design and propose a solution for a computerized data archiving information system to address the manual archiving system problem at the Abie Property office. The software development method used is the Incremental Model, which allows system implementation to be carried out in stages according to priority needs. This study uses descriptive methods and data collection techniques through observation, interviews, and direct document studies. The results of the research analysis concluded that the manual system hampers efficiency, causing the risk of losing, duplicating, and being unable to find documents. The system design includes Entity Relationship Diagrams (ERD), Data Flow Diagrams (DFD), Use Case Diagrams, as well as interface and database designs. It is expected that the implementation of this system will increase archiving efficiency by up to 70%, reduce archive search time by up to 80%, and facilitate strategic decision making through structured and real-time data access. This research practically contributes to digitalization for small and medium property businesses, and academically as a case study of the application of the Incremental Model of Information Systems in Document Management Systems.